Optimization of Consumer Satisfaction and Its Impact on KFC Kakialy Customer Loyalty - Jacsy Tubalawony; Walter Tabelessy; Merry Margareth Pelupessy (ProBisnis : Jurnal Manajemen, 2023)
This study tries to analyze the optimization of consumer satisfaction which is influenced by customer value and business location and its impact on KFC Kakialy customer loyalty. Using a purposive sampling technique, a structured questionnaire as a characteristic of quantitative research was distributed to 160 respondents. The GSCA statistical technique with the help of the GSCA Pro application version 1.1.8 was used to analyze the research data. Through the evaluation of the measurement model it proves that all the indicators used have good validity. And through the evaluation of the structural model it proves that all the hypotheses proposed are acceptable, namely customer value has a positive and significant effect on customer satisfaction, business location has a positive and significant effect on customer satisfaction, and consumer satisfaction has a positive and significant effect on customer loyalty. And through the evaluation of the overall model it was found that the research model was fit.